Facile Synthesis of Ternary g-C3N4@BiOCl/Bi12O17Cl2 Composites With Excellent Visible Light Photocatalytic Activity for NO Removal - Zhang, Wendong; Liang, Yi (Frontiers in Chemistry, 2019)
In this study, novel two-dimensional (2D) g-C3N4@BiOCl/Bi12O17Cl2 composites have been fabricated through a facile deposition-precipitation process. The as-prepared photocatalysts were characterized by XRD, SEM, TEM, XPS, UV-vis DRS, PL, Photocurrent, EIS, ESR, and N2 adsorption-desorption. The photocatalytic activities were investigated through NO removal test in gas under visible light irradiation (λ>420 nm). The g-C3N4@BiOCl/Bi12O17Cl2 composites exhibit enhanced visible light absorption and photo-induced electron-hole separation efficiency, compared with pristine g-C3N4 and BiOCl/Bi12O17Cl2. The intimated contact interfaces between g-C3N4 and BiOCl/Bi12O17Cl2 nanosheets are responsible for the more efficient photochemical interactions. The present work provides a new derection to develop a class of ternary g-C3N4-based visible-light-driven photocatalysts for environmental purification.